The influence of self efficacy and providing incentives on increasing employee engagement at PT. Remco Rubber Indonesia - Iqbal Puza Rama; Endah Dewi Purnamasari; Mohammad Kurniawan D P (Enrichment : Journal of Management, 2023)
Employee engagement reflects the involvement and enthusiasm of employees in their work and workplace. Employees are engaged when their basic needs are met, and when they have opportunities to contribute, a sense of belonging, and opportunities to learn and develop. Employees with good engagement, will be very enthusiastic about their work and workplace. This study aims to examine the effect of self-efficacy and provision of incentives on increasing employee engagement. A total of 221 respondents were collected by distributing questionnaires to all employees at PT. Remco Rubber Indonesia using non-probability sampling technique. The analysis technique used is a mixed technique, namely quantitatively from the results of distributing questionnaires, and qualitatively from the results of interviews with the recommended five respondents. The results of the analysis show that partially self-efficacy and provision of incentives each have a positive and significant effect on increasing employee engagement (prob = 0.000 < alpha = 0.05). And simultaneously, that the variables of self-efficacy and provision of incentives together have a positive effect on increasing employee engagement (prob = 0.00 < alpha = 0.05).